PENGARUH KUALITAS PRODUK, HARGA PRODUK DAN KEAMANAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pasar Tradisional Madyopuro Kota Malang) - Nukman Nador; Nur Hidayati; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe purpose of this study was to determine the effect of the product quality, price, and product safety on purchasing decisions at Madyopuro Traditional Market Malang. The sample in this study were 70 consumers with established criteria. The analytical method used in this study is multiple linear regression analysis with hypothesis testing using t test and F test. From this study provides result and shows that there is partial and simultaneously a relationship or influence between product quality, product price, and product safety on purchasing decisions.Keywords : product quality,product price, and product safety.